Archiving Metaxourgio - Thomais Kordonouri (Joelho)
‘Archive’ is a totality of records, layers and memories that are collected. A city is the archive that consists of the conscious selection of these layers and traces of the past and the present, looking towards the future. Metaxourgio is an area in the wider historic urban area of Keramikos in Athens that includes traces of various eras, beginning in the Antiquity and continuing all the way into the 21st century. Its archaeological space ‘Demosion Sema’ is mostly concealed under the ground level, waiting to be revealed. In this proposal, Metaxourgio is redesigned in light of archiving. Significant traces of the Antiquity, other ruins and buildings are studied, selected and incorporated in the new interventions. The area becomes the ‘open archive’ that leads towards its lost identity. The proposal aims not only to intensify the relationship of architecture with archaeology, but also to imbue the area’s identity with meanings that refer to the past, present and future.